Probabilistic reduction and probabilistic enhancement: Contextual and paradigmatic effects on morpheme pronunciation - Cohen, Clara (Morphology (Dordrecht), 2014)
Research on probabilistic pronunciation variation has generally focused on contextual probability , or the probability of using a linguistic unit (segment, syllable, word, etc.) in the context of a particular utterance. Overwhelmingly, this research has found that higher contextual probability leads to phonetic reduction. Less attention, however, has been given to paradigmatic probability , or the probability of using a particular linguistic form from a paradigm of related forms. The research that has addressed this type of probability has found inconsistent results: Sometimes higher paradigmatic probability leads to phonetic enhancement, and sometimes to phonetic reduction. In this paper I present the results of an experiment exploring the effects of both types of probability simultaneously on the pronunciation of agreement suffixes on English verbs. I find that (i) singular verb suffixes and stems are phonetically reduced when singular agreement is contextually probable; (ii) the nature of the reduction is modulated by verb frequency, consistent with dual-route models of lexical retrieval; and (iii) suffixes are phonetically enhanced when they are paradigmatically probable. I conclude by discussing how the patterns observed in this study shed light on the previous contradictory findings regarding the effects of paradigmatic probability on pronunciation.